2018
DOI: 10.1093/infdis/jiy393
|View full text |Cite
|
Sign up to set email alerts
|

Human Biomarkers of Outcome Following Rift Valley Fever Virus Infection

Abstract: Rift Valley fever virus is an arbovirus found in Africa and the Middle East. Most infected individuals experience a mild self-limiting illness; however, some develop severe disease including hepatitis, hemorrhagic fever, or encephalitis. The biological reasons for these marked differences in disease manifestation are unknown. In this study, we evaluate 32 biomarkers in serum of 26 patients from an outbreak that occurred in Saudi Arabia in 2000-2001. Eleven biomarkers correlated with viral RNA. Thirteen biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Haemorrhage is also caused by direct viral invasion and damage to the endothelial cells and thrombocytopenia. The elevation in hepatic transaminases has previously been associated with a fatal outcome [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Haemorrhage is also caused by direct viral invasion and damage to the endothelial cells and thrombocytopenia. The elevation in hepatic transaminases has previously been associated with a fatal outcome [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…In all host species, innate immunity is a key component of early RVFV detection and activation of further effector cells, e.g., macrophages, via release of cellular mediators including IFNs [24,27,34,45,70]. The B6-IFNAR tmAgt mice lack the IFN type I receptor (IFNAR) and showed severe RVF characterized by severe clinical signs, necrotizing hepatitis and virus spread to various organs as described previously [37,50].…”
Section: Discussionmentioning
confidence: 75%
“…Thus, they play a key role as pattern recognition receptors in many viral infections, e.g., the RVFV-related Punta Toro virus for which was shown that TLR 3 could even induce detrimental effects due to overstimulation [30][31][32]. Furthermore, it has been shown that genetic polymorphisms of TLR 7 correlate with RVF severity in humans; thus, it can be assumed that TLR 3 and 7 are relevant elements of RVFV recognition [33,34]. The interferon response is counteracted by RVFV via its major pathogenicity factors, the non-structural proteins s (NSs) and m (NSm) [24,[35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Lymphopenia (measured by both methods) occurred by 1 dpi through 5 dpi in both groups, but the SC-infected rats returned to baseline levels quicker while AERO-infected rats only partially recovered. Lymphopenia and granulocytosis are documented findings during lethal RVF infection, in both animal models and human clinical samples [8, 1922]. These data provide a direct comparison of changes in the peripheral blood between SC vs AERO infection routes and also serve to validate both the CBC analysis and flow cytometry as complementary methods for blood cell typing in rats.…”
Section: Resultsmentioning
confidence: 87%